Implementation of Collaborative Writing by Using Padlet to Improve Writing Descriptive Text - Utami, Pertiwi Putri; Barathayomi, Wieka; Evenddy, Sutrisno Sadji (Journal of Linguistics, Literacy, and Pedagogy, 2022)
The research aims to know the learning process of writing descriptive text using collaborative writing and Padlet and the improvement of writing descriptive text using collaborative writing and Padlet. The researcher used a qualitative-quantitative approach with classroom action research, collaborated with an English teacher from SMAN 24 Kabupaten Tangerang. The participants in this research were 18 students from class 10 IPS 4 at SMAN 24 Kabupaten Tangerang. The action research was conducted in two cycles, with steps from planning, action, observing, and reflecting. To obtain the data, the researcher used observation sheets, documentation, and written test. The result of the research showed that there was an improvement in students’ writing results after conducting collaborative writing by using Padlet. The total presentation of students who pass the passing grade was improved from 38.89% in the pre-test, 55.50% in post-test cycle 1, to 83.33% in post-test cycle 2. While for the mean score of the class, also improved from 63.11 in the pre-test, 68.17 in cycle 1, to 80.50 in cycle 2.